Hungarian Question Discussed on the Last Day of the 12th Session - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Strong attack was made on the governments of the Soviet Union and Hungary. Discussion ended in shrill discord and continued differences. Neue Zürcher Zeitung report.